1983
DOI: 10.1136/bjsm.17.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the prognosis of meniscectomy in soccer players.

Abstract: Meniscectomy is a frequent surgical procedure in young soccer players but the results are unpredictable. A long-term survey was carried out to assess certain fundamental features and to establish the predictive factors which affect the prognosis after meniscectomy. INTRODUCTIONMore than a third of all meniscal injuries occur in sport of which soccer accounts for 69% (Smillie, 1970). However, the results of this procedure can vary enormously due to many factors such as an associated ligamentous injury, the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In this study, the mean age at which surgery occurred was significantly lower for the ankle (26.4 years) and knee (28.0 years) joints than for the hip joints (37.5 years) by 10 years. Muckle 36 reported that the average age for knee surgery in a group of 50 professional and 41 non-professional soccer players was 23.9 years and that each of these players was also diagnosed with OA within 10 years of surgery.…”
Section: Represented a Relatively Smallmentioning
confidence: 99%
“…In this study, the mean age at which surgery occurred was significantly lower for the ankle (26.4 years) and knee (28.0 years) joints than for the hip joints (37.5 years) by 10 years. Muckle 36 reported that the average age for knee surgery in a group of 50 professional and 41 non-professional soccer players was 23.9 years and that each of these players was also diagnosed with OA within 10 years of surgery.…”
Section: Represented a Relatively Smallmentioning
confidence: 99%
“…Historically, professional soccer players with symptomatic meniscal tears have been treated with meniscectomy in order to RTP, free of symptoms, as soon as possible. [50][51][52] Partial meniscectomy may allow early RTP at 6 to 8 weeks at the preinjury level in the majority of professional athletes. 9 , 24 Resection of meniscal tissue, besides having established long-term consequences predisposing patients to early knee osteoarthritis, 6 , 10 in the setting of lateral partial meniscectomy may lead to rapid chondrolysis of the lateral compartment.…”
Section: Discussionmentioning
confidence: 99%
“…In his analysis of 91 soccer players who had undergone meniscectomy (either partial or total), Muckle found that all had developed radiological changes of knee osteoarthritis within 10 years of meniscectomy. 10 Chantraine, in a study of 81 former soccer players, showed that all 42 knees that had undergone excision of at least was 3.6 times (95% CI, 0.8-16.2; P=0.10) and 17.7 times (95% CI, 2.2-146.2; P=0.0075), respectively.…”
Section: Controlsmentioning
confidence: 99%